Ethnic diversity and conflict - Bleaney, Michael; Dimico, Arcangelo (Cambridge University Press, 2016)
We argue that the reason why it has proved hard to determine whether negative effects on economic performance and conflict are more strongly associated with polarized rather than fractionalized societies is because the distinction between polarization and fractionalization is only relevant for societies with ethnic diversity above a certain threshold. In addition, high levels of ethnic fractionalization at a country level are generally associated with regional concentration of minorities, and as a result, many regions may have a very different ethnic composition from the national average, and in particular, they may have much higher levels of ethnic polarization than the national level. Because of the very different ethnic composition of different regions in this situation, conflict is more likely to be confined to a limited geographical area.